2014
DOI: 10.4049/jimmunol.1300631
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Targeting Alters Regulation of Expression and Antigen Presentation of Proinsulin

Abstract: Peptide ligands presented by MHC class I (MHC-I) molecules are produced by degradation of cytosolic and nuclear, but also endoplasmic reticulum (ER)–resident, proteins by the proteasome. However, Ag processing of ER proteins remains little characterized. Studying processing and presentation of proinsulin, which plays a pivotal role in autoimmune diabetes, we found that targeting to the ER has profound effects not only on how proinsulin is degraded, but also on regulation of its cellular levels. While proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…From a therapeutic point of view, PIs did not induce T cell activation and selectively promoted the generation of innate immune cytokines. There is a possibility that a PI will influence antigen presentation (35) and therefore may prevent it from triggering the immune system to clear latent HIV reservoirs. This should be taken into consideration when assessing the feasibility of LRAs.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic point of view, PIs did not induce T cell activation and selectively promoted the generation of innate immune cytokines. There is a possibility that a PI will influence antigen presentation (35) and therefore may prevent it from triggering the immune system to clear latent HIV reservoirs. This should be taken into consideration when assessing the feasibility of LRAs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely accepted that degradation products of newly synthesized proteins are the source for epitopes presented to CD8 + T-cells in MHC class I molecules. Decreasing proinsulin degradation in pancreatic β-cells therefore potentially opens new avenues for treatment of type 1 diabetes, as blocking proinsulin degradation may affect the presentation of proinsulin-derived epitopes via MHC class I molecules to CD8 + T-cells [ 45 ]. Prevention of ERAD through small compounds like eeyarestatin may decrease proinsulin degradation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ppins75–99 (C18-A10) domain also contained overlapping (nested) immunodominant HLA-DRB*0401-restricted epitopes (i.e., C13-C32, C19-A3 and C22-A5) 50 , indicating that this domain is efficiently processed for MHC class II epitope presentation. Structural features and/or intrinsic expression of ppins designer antigens could affect processing and MHC class I- and class II- epitope presentation 40 51 . We previously showed that the expression of mutant ppinsΔA 12-21 and ppins differed substantially in transiently transfected HEK-293 cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines against self-proteins contain a non-predictable risk to induce or stimulate autoreactive T cell responses rather than a protective immunity in individual recipients. Factors like MHC I and II composition or genetic factors, but also antigen expression and processing could influence the priming of immune responses 40 51 . We here showed that the ppinsΔA 12-21 antigen (lacking the dominant K b /A 12-21 epitope) induced Treg cells in PD-L1 −/− and PD-1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%